Trait emotional intelligence anchored within the Big Five, Big Two and Big One frameworks - Perez-Gonzalez, Juan Carlos (2014)
This paper investigates the relationship between trait emotional intelligence (trait EI) and the Big Five factors, the Big Two and the Big One (i.e., General Factor of Personality; GFP). Comprehensive measures of trait EI (TEIQue) and the Big Five (NEO-PI-R) were applied to a sample of 289 university students (170 female). As expected by the trait EI theory, part of the construct’s variance was explained by a linear combination of the Big Five, while a distinct oblique trait EI factor was isolated in the Big Five factor space, in line with previous research. Trait EI positively correlated with the Big Two, namely Alpha/Stability and Beta/Plasticity. Finally, correlations between trait EI and the GFP were higher than those between GFP and the Big Five factors from which it was extracted. In addition, when GFP was extracted from the joint data set combining the Big Five factors of the NEO-PI-R and the dimensions (factors or facets) of the TEIQue, the highest loadings came from the latter, not from the former. Findings support the view that trait EI is a broad personality trait integrated into multi-level personality hierarchies and the idea that trait EI can be considered as a proxy of the GFP.